Association and risk of blood urea nitrogen-to-creatinine ratio with congestive heart failure in critically ill COPD patients - Jinjun Sun; Weiwei Chen; Hongli Xu (BMC Pulmonary Medicine)
Abstract Objective Chronic obstructive pulmonary disease (COPD) is a leading cause of global morbidity and death. The blood urea nitrogen-to-creatinine ratio (BCR) is recognized as a crucial marker to assess renal function and cardiovascular risk. Nevertheless, the effects of BCR on COPD patients suffering comorbid congestive heart failure (CHF) is not clarified. This study aims to elucidate the association between BCR and CHF risk in the COPD population. Methods Data from COPD patients meeting the eligibility criteria were from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The cumulative incidence curve was utilized for examining the link of BCR to CHF. Kaplan-Meier (KM) analysis was carried out for evaluating the relation of BCR to in-hospital mortality(IHM). Multivariable Cox regression assisted in assessing the correlation of BCR with CHF risk. Restricted cubic splines (RCS) were leveraged for unraveling the association of BCR (as a continuous variable) with CHF. Results Our study included 2,840 COPD patients in the intensive care unit for the first time, with hospital stays exceeding 24 h. The incidence of CHF was 57.18% among these patients. Cumulative incidence curve analysis demonstrated a notably increased CHF incidence in patients having higher BCR (18.889 < BCR ≤ 92.5) in contrast to those with lower BCR (2.877 ≤ BCR ≤ 18.889) (p < 0.0001). KM survival analysis indicated a markedly elevated IHM risk in patients with higher BCR in comparison to those with lower BCR (p < 0.0001). Multivariable Cox regression and RCS analysis further confirmed that higher BCR was linked to a risen likelihood of CHF [hazard ratio (HR) = 1.28, 95% confidence interval (CI, 1.15–1.44), p < 0.001]. Subgroup analysis revealed a higher risk of CHF [HR = 1.41, 95% CI (1.13–1.76), p = 0.002] in patients with diabetes than those without [HR = 1.24, 95% CI (1.08–1.41), p = 0.002]. Conclusion Elevated BCR is an independent risk factor for CHF in critically ill COPD individuals and strongly related to a risen risk of CHF. The findings prove BCR as a reliable clinical predictor, facilitating risk stratification and personalized treatment for COPD patients with comorbid CHF.